INVESTIGATION OF LASER TEXTURING ON THE SURFACE OF ANODIZED ALUMINIUM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This study examines the texturing of anodized aluminium using a Rofin PowerLine F 20 Varia nanosecond Yb doped fiber laser. It explores how varying laser parameters like scanning speed, hatching step, laser power, and frequency impact the surface's wetting properties, particularly the contact angle with a water droplet. The research aims to understand the influence of these parameters on the aluminium’s surface, offering insights into the laser micromachining process and its industrial and material science applications. This study examines the texturing of anodized aluminium using a Rofin PowerLine F 20 Varia nanosecond Yb doped fiber laser. It explores how varying laser parameters like scanning speed, hatching step, laser power, and frequency impact the surface's wetting properties, particularly the contact angle with a water droplet. The research aims to understand the influence of these parameters on the aluminium’s surface, offering insights into the laser micromachining process and its industrial and material science applications. This study investigates the texturing of anodized aluminium using a Rofin PowerLine F20 Varia nanosecond fiber laser. It investigates how different laser parameters such as scan speed, hatching step, laser power and frequency affect the surface wetting properties, especially the contact angle of a water droplet. The research aims to understand the influence of these parameters on the aluminium surface, offering insights into the laser micromachining process and its applications in industry and materials science.